Standardizing Phenotyping Technique for Drought Stress Assessment in Teak, Combining Morpho-physiology and Biochemical Indices - Ashwath, M. N.; Santhoshkumar, A. V.; Ankita; Shiran, K.; Mohapatra, Sourav Ranjan; Binu, N. K. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted in the month of August, 2023 at the College of Forestry, Kerala Agricultural University, Kerala, India to identify the peak drought stress period and optimize phenotyping techniques for drought tolerance screening in teak seedlings under tropical humid conditions. The experiment subjected eight-month-old vegetatively propagated teak seedlings to controlled drought conditions over 20 days. Morpho-physiological parameters such as number of leaves, relative water content (RWC), photosynthetic rate, stomatal conductance, transpiration rate, and chlorophyll fluorescence were monitored bi-daily. The results revealed that the 9th and 10th days after withholding irrigation marked the maximum drought stress period, with significant reductions in photosynthesis (0.372 mole CO2 m-2 s-1), stomatal conductance, and RWC (51.14%). Biochemical analysis showed increased levels of proline, glycine betaine, and total soluble sugars, confirming stress adaptation. Upon rewatering, partial recovery was observed in physiological traits, while biochemical markers indicated ongoing stress response adjustments. Correlation and regression analyses highlighted strong interrelations between photosynthesis and traits such as stomatal conductance, RWC, and chlorophyll fluorescence. The findings were revalidated through repeated trials, confirming the 10th day as the optimal time for drought phenotyping in teak seedlings in given condition. This study enhances our understanding of teak’s drought response and offers critical insights for breeding programs and sustainable plantation management strategies.